Biporous Crosslinked Polymers With Controlled Pore Size and Connectivity. Issue 1 (July 2016) - Ly, Hai Bang; Halbardier, Lucile; Grande, Daniel
Summary: A critically selected overview of different parameters affecting the porous features of doubly porous polymeric materials based on poly(2‐hydroxyethyl methacrylate) (PHEMA) and designed via a double porogen approach is addressed. A careful investigation was undertaken so as to highlight the main advantages of the proposed double porogen approach which relied on the distinct and independent control of both porosity levels, i.e . nano‐ and macro‐porosity. The nanoporosity level was produced via a phase separation phenomenon that occurred during the polymerization process in the presence of a porogenic solvent. To generate an interconnected macroporosity, two straightforward and versatile strategies were implemented through the use of sodium chloride (NaCl) macro‐sized particles. They involved the sintering of NaCl particles prior to the generation of PHEMA‐based networks. NaCl particles were fused through two different methods, either by sintering at 730 °C or by Spark Plasma Sintering. Upon porogen removal, doubly porous PHEMA‐based materials were obtained with macropores having NaCl particle imprints in the 100 μm order of magnitude, while the second porosity level laid within the 0.1–1 μm orders of magnitude, as evidenced by mercury intrusion porosimetry and scanning electron microscopy.